The Study of Constructivistic Learning Experience, Democratic Attitude, Learning Independence & Learning Motivation of Senior High School Students at Wajo Regency South Sulawesi - Muhammad Arafah; Syamsu Rijal; Sumarni; Suriyah Satar; Besse Sulfiani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study employs a quantitative survey method with correlation analysis to investigate the influence of constructivist biology learning experiences, democratic attitudes, and learning independence on the learning motivation of high school students in Wajo Regency. The research utilizes Structural Equation Modeling (SEM) for path analysis to determine the direct and indirect effects among the studied variables. The population comprises all high school students in Wajo Regency, with a sample of 274 students selected through simple random sampling from three schools: SMAN 1 Wajo, SMAN 3 Wajo, and SMAN 7 Wajo. Data were collected using four validated instruments: a 35-item constructivist biology learning experience questionnaire, a 30-item democratic attitude questionnaire, a 49-item learning independence questionnaire, and a 30-item learning motivation questionnaire. Descriptive analysis reveals that the average scores for constructivist learning experience, democratic attitudes, learning independence, and learning motivation are 66.16%, 67.56%, 70.79%, and 72.35%, respectively. SEM results show that constructivist biology learning experiences positively influence learning motivation (path coefficient = 0.228), as does learning independence (path coefficient = 0.430). In contrast, democratic attitudes exhibit a significant negative influence on learning motivation (path coefficient = -0.645). These findings highlight the critical role of active, student-centered learning approaches and learner autonomy in enhancing motivation. Interestingly, the negative correlation between democratic attitudes and learning motivation suggests a complex relationship that may reflect contextual or cultural factors specific to the student population. This study contributes to the field of educational psychology by emphasizing the effectiveness of constructivist pedagogical strategies and the promotion of student independence in motivating learners. The results provide practical implications for educators and policymakers seeking to improve motivation and learning outcomes through the design of more effective instructional practices.